Care for patients living with chronic conditions using the ICAN Discussion Aid: A mixed methods cluster-randomized trial. - Kasey R Boehmer; Anjali Thota; Paige Organick-Lee; Megan Branda; Alex Lee; Rachel Giblon; Emma Behnken; Hazel Tapp; Carl May; Victor Montori (PLoS ONE)
Objectives To assess the effectiveness of the ICAN Discussion Aid in improving patients' experience of receiving care for their chronic conditions and health professionals' experience of providing their care. Methods We conducted a pragmatic, mixed-methods, cluster-randomized trial of the ICAN Discussion Aid at 8 clinics in 4 independent health systems in the US from January 2017 and to August 2018. Sites were randomized 1:1 in pairs. Participants were primary care health professionals and their adult patients with ≥1 chronic condition. Quantitative outcomes were health professional assessment of chronic illness care and relational coordination and patient-reported self-efficacy to manage chronic disease, self-efficacy to communicate with clinician, treatment burden, assessment of chronic illness care, general health, and disruption from illness and treatment. Uptake of ICAN was assessed with patient qualitative interviews, clinician focus groups/interviews, visit video recordings, and chart review. Results 98 clinicians and 1733 patients participated. We found no significant differences between ICAN and usual care sites in mixed effect models on main outcome measures. In adjusted difference-in-differences analyses, we found patient self-efficacy to manage chronic disease (mean difference 0.61 (SE 0.27), p = 0.023), patient self-efficacy to communicate with their clinician (mean difference 0.31 (SE 0.14), p = 0.032), and health professional assessment of chronic illness care (1.42 (SE 0.52), p = 0.007) were significantly better at ICAN sites. Chart review indicated the aid was implemented in 19% of eligible encounters. Qualitative analyses highlighted limited implementation of ICAN as intended overall due to varying clinic challenges but showed that ICAN use as intended was a valued addition to the visit. Conclusions When patients and clinicians use ICAN as intended, which seldom occurred, important conversations emerge. This qualitative finding did not parlay into statistically significant effects on most outcomes of interest. Trial registration The trial was registered at clinicaltrials.gov (# NCT03017196).